Impressive reduction of brain metastasis radionecrosis after cabozantinib therapy in metastatic renal carcinoma: A case report and review of the literature - Lolli, Jacopo; Tessari, Francesca; Berti, Franco; Fusella, Marco; Fiorentin, Davide; Bimbatti, Davide; Basso, Umberto; Busato, Fabio (Frontiers in Oncology, 2023)
Introduction Radionecrosis is a consequence of SRS (Stereotactic Radiosurgery) for brain metastases in 34% of cases and, if symptomatic (8-16%), it requires therapy with corticosteroids, bevacizumab and less frequently surgery. Oncological indications are increasing and appropriate stereotactic adapted LINACs (Linear Accelerators) are becoming more widespread available worldwide. Efforts are being made to treat brain radionecrosis in order to relieve symptoms and spare the use of active therapies. Case Presentation Herein we describe a 65-year-old female patient presenting with brain radionecrosis 6 months after stereotactic radiotherapy for two brain metastatic lesions. Being symptomatic with headache and cognitive-motor slowing, the patient received corticosteroids. Because of later lung progression, the patient passed to Cabozantinib. An impressive reduction of the two brain radionecrosis areas was seen at the brain MRI 2 months after the initiation of the angiogenic drug. Discussion The high incidence of radionecrosis (2/2 treated lesions) can be interpreted by the combination of SRS and previous Ipilimumab that is associated with increased risk of radionecrosis. The molecular mechanisms of brain radionecrosis are poorly understood nor its exact duration in time. We hypothesize that the anti-angiogenic effect of Cabozantinib may have had a strong effect in reducing the brain radionecrosis areas. Conclusion In this clinical case, Cabozantinib is associated with a fast and significant volume reduction of brain radionecrosis appearing after SRS and concomitant immunotherapy. This drug seems to show, like Bevacizumab, clinical implications not only for its efficacy in systemic disease control but also in reducing brain radionecrosis. More research is needed to evaluate all molecular mechanisms of brain radionecrosis and their interaction with systemic therapies like third generation TKIs.